2006
DOI: 10.1017/s002211200600019x
|View full text |Cite
|
Sign up to set email alerts
|

Coherent structures and turbulent molecular mixing in gaseous planar shear layers

Abstract: Quantitative planar visualization of molecular mixing dynamics in large- and intermediate-scale coherent structures is reported for the first time in the developing and far-field regions of gaseous planar shear layers. A dual-tracer (nitric oxide and acetone) planar laser-induced fluorescence (PLIF) technique is implemented as the gaseous analogue to acid/base chemical reactions that have previously been used to study molecular mixing in liquid shear layers. Data on low-speed, high-speed, and total molecularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Using the cold-chemistry technique, where NOfluorescence is quenched when mixed with oxygen, Clemens and Paul [13] found values for the mixed fluid fraction of δ m /δ t = 0.45 at a convective Mach number of 0.35, and a value of δ m /δ t = 0.48 at a convective Mach number of 0.82. For top-stream velocities below 50 m/s, Meyer et al [16] found decreasing mixing with increasing top-stream velocity (Reynolds number) with values ranging from δ m /δ t = 0.58 at U 1 = 29.5 m/s and U 2 = 12.8 m/s to δ m /δ t = 0.55 at U 1 = 50.5 m/s and U 2 = 12.8 m/s using an improved dual-tracer cold-chemistry technique. These data show a decrease in mixing with increasing top-stream velocity that, if extrapolated, would give mixing efficiencies close to the fast-chemistry results.…”
Section: Mixing With Expansion-ramp Injectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the cold-chemistry technique, where NOfluorescence is quenched when mixed with oxygen, Clemens and Paul [13] found values for the mixed fluid fraction of δ m /δ t = 0.45 at a convective Mach number of 0.35, and a value of δ m /δ t = 0.48 at a convective Mach number of 0.82. For top-stream velocities below 50 m/s, Meyer et al [16] found decreasing mixing with increasing top-stream velocity (Reynolds number) with values ranging from δ m /δ t = 0.58 at U 1 = 29.5 m/s and U 2 = 12.8 m/s to δ m /δ t = 0.55 at U 1 = 50.5 m/s and U 2 = 12.8 m/s using an improved dual-tracer cold-chemistry technique. These data show a decrease in mixing with increasing top-stream velocity that, if extrapolated, would give mixing efficiencies close to the fast-chemistry results.…”
Section: Mixing With Expansion-ramp Injectionmentioning
confidence: 99%
“…One flow geometry that can produce efficient mixing between two streams is the shear or mixing layer [5][6][7][8][9][10][11][12][13][14][15][16]. The geometry can be tailored to mitigate pressure gradients in the flow and minimize total-pressure losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies in the past 40 years acquired abundant evidence and data supporting the dynamical role of CS. CS control entrainment and mixing of species (Dimotakis & Brown 1976, Dutton & Lucht 2006, and contribute comparable amount to the Reynolds stresses and heat flux as does random turbulence (Hussain & Zaman 1985, Antonia et al 1986). The Reynolds stresses may take negative values in the region of positive mean-flow gradient, indicating that closure models of the mean-flow gradient type are inappropriate.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant results is a detection of a sharp increase of mixing rates caused by the onset of small-scale turbulence within large-scale coherent motions [14]. This effect that was studied experimentally and numerically, demonstrates complex nonlinear dynamics of mixing (see, e.g., [8,11,15,16,17,18]). However, it is not clear how such mixing states are attained, and the ambiguity is exacerbated by the differences in experimental results.…”
Section: Introductionmentioning
confidence: 96%